Hybridization of 2D MoS2 Nanoplatelets and PtAu Hybrid Nanoparticles for the SERS Enhancement of Methylene Blue (Adv. Mater. Interfaces 21/2021). Issue 21 (10th November 2021) - Lin, Shusen; Mandavkar, Rutuja; Kulkarni, Rakesh; Pandit, Sanchaya; Burse, Shalmali; Habib, Md Ahasan; Kunwar, Sundar; Lee, Jihoon
Abstract : Hybrid SERS Platform In article number 2101084, Shusen Lin, Sundar Kunwar, Jihoon Lee, and co‐workers demonstrate a hybrid surface enhanced Raman spectroscopy (SERS) platform by hybridizing the MoS2 nanoplatelets and core‐shelled PtAu hybrid nanoparticles (HNPs) for the SERS enhancement of methylene blue. The unique morphology of PtAu core‐shell HNPs, namely the core‐shelled PtAu NPs along with the high density background Au NPs, can offer strong localized surface plasmon resonance and high density hot spots.